Analisis Strategi Bisnis UMKM melalui Pemanfaatan Media Sosial Tiktok Shop - Meci Nilam Sari; Rika Septrizarty; Wila Farlina; Azmen Kahar; Agus Nurofik (Journal of Economics and Management Scienties, 2023)
During the Covid-19 pandemic, it was a period where initially all business sectors experienced a decline, starting from turnover, creativity and innovation in products, packaging, and efforts to promote business development in Indonesia. MSMEs in the city o f Padang are starting to move into their business activities, which initially started as an offline shop/door to door, now they have turned into an online shop. Every business owner must do an online shop because of the impact of the pandemic. the times from day to day are always included in terms of business promotion by using the Tik Tok Shop for MSMEs in the city of Padang. With this convenience, consumers do not need to be tired of spending time, transportation money to shop at the market or mall because all products are provided in one Tiktok shop application and free shipping is delivered directly to consumers' homes.